Evaluación Financiera a la Planta de Lácteos Ecolac Cia. Ltda. de la Ciudad de Loja en el Período 2013-2014 - Cuenca Remache, Valeria Katherine (2016)
The thesis entitled "FINANCIAL ASSESSMENT OF DAIRY PLANT ECOLAC CIA. LTDA LOJA CITY IN THE PERIOD 2013-2014 " was held for the purpose of choosing the title of Engineer in Accounting and Auditing, the same who was executed in accordance with the Regulation of Academic Board of the National University of Loja, for I make known the economic and financial development of the company, which will serve as the basis for future decisions correct, that lead to administrative functioning of it for which I run based on both general and specific objectives. Referring to the first specific objective: Perform financial structure through the horizontal and vertical analysis with the application of indicators to objectively interpret accounting information, where the economic and financial structure was determined, presenting in 2014, Active Power with 51.49% 48.51% non-Current Assets, Current Liabilities 36.81% 40.09% non-current Liabilities and Equity of 23.10%. In the horizontal analysis the increase and decrease of accounts that has taken place in this economic period is determined, the most representative variation of Active Accounts and notes receivable from related entities in 2014 presenting a decrease of 90.54% this is because customers have canceled debts owed to the company, the liabilities have Accounts and 6 notes payable to related with an increase of 87.43% for the new obligations that the company acquired entities related entities and finally the Heritage, it has not undergone any variation within periods, In applying the indicators according to the nature of the economic activity of the company it follows that account in 2014 with a liquidity of $ 1.40 an inventory turnover of 21.19 times indebtedness of 77%, and a return on sales of 11.95%. The second specific objective is: Follow the cash budget, pro forma financial statements with application of indicators, Net Present Value (NPV), Internal Rate of Return (IRR), payback period of capital, sensitivity analysis, and cost-benefit ratio. Forecasts of revenue and expenditure of the company for the economic and administrative method was applied, based substantiate to reach prepare the cash budget and therefore obtaining Projected Financial Statements Loss of $ 30,346.55 in 2015 and $ 8,604.37 in 2016, while in 2017 shows income of $ 7.937,24, in 2018 for $ 21,240.41, and in 2019 of $ 34,545.91; where the balance point according to the installed capacity of 91.59%, 79.20%, 69.71% respectively for the three years that the company generates income where not win or lose. With the above data indicators Financial Evaluation coming to get a Net Present Value (NPV) of $ 47.390,67, the Internal Rate of Return (IRR) 7 43.84%, and the recovery period of 2 years 3 was applied months 4 days, the cost benefit of $ 1.02 and Sensitivity Analysis where costs can increase by 0.66% and revenue decreased 0.65%. The third specific objective is to: Prepare a report of the financial evaluation applied based on the results, which will support the company executives also critical points where it was determined that the company has a debt level are set high due to commitments with third parties, the same that have originated from the activities, jeopardizing the economy of the company. The methodology used is based on the Scientific, Deductive, Inductive, Synthetic, and Analytical, Mathematical methods, which facilitated the collection of information, critical to meeting the target, analysis and interpretation of the results obtained in the present thesis.